2014
DOI: 10.1177/1098612x14563097
|View full text |Cite
|
Sign up to set email alerts
|

Survey of dietary and medication practices of owners of cats with chronic kidney disease

Abstract: The objective of this study was to describe the dietary and medication patterns of cats with chronic kidney disease (CKD). In this prospective, cross-sectional descriptive study, owners of cats with CKD were asked to complete a web-based survey. The study was advertised on CKD-, pet-, veterinary- and breed-associated websites and list serves. Owners of 1089 cats with CKD participated in the study. The mean reported age of the cats with CKD was 13.7 ± 4.2 years. Forty percent (430/1089) of cats had concurrent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…However, in a recent study, acid suppressants did not influence the probability of survival to discharge . In studies of healthy dogs and cats, twice‐daily administration of acid suppressants did not achieve the target of pH > 6 for a prolonged period . More studies are warranted to determine the efficacy and optimal dosage of acid suppressants for the treatment of thrombocytopenic‐induced GI bleeding in dogs and cats.…”
Section: Evidence To Support Clinical Use Of Gastroprotectants In Dogmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in a recent study, acid suppressants did not influence the probability of survival to discharge . In studies of healthy dogs and cats, twice‐daily administration of acid suppressants did not achieve the target of pH > 6 for a prolonged period . More studies are warranted to determine the efficacy and optimal dosage of acid suppressants for the treatment of thrombocytopenic‐induced GI bleeding in dogs and cats.…”
Section: Evidence To Support Clinical Use Of Gastroprotectants In Dogmentioning
confidence: 93%
“…Moreover, in a recent study of 10 cats with chronic renal disease and 9 healthy age‐matched control cats, no significant differences were observed in serum gastrin concentrations and gastric pH between groups, suggesting that cats with CKD may not have gastric hyperacidity compared to healthy cats, and therefore, may not need acid suppression . However, despite this evidence, acid suppressants are commonly prescribed to dogs and cats with CKD . Chronic administration of acid suppressants to dogs and cats with CKD may not be benign.…”
Section: Evidence To Support Clinical Use Of Gastroprotectants In Dogmentioning
confidence: 99%
“…Terminology in the veterinary literature regarding decreased appetite is highly variable and often nonspecific (e.g, “anorexia,” “poor appetite,” “decreased appetite”). Retrospective studies providing data on decreased appetite in cats with CKD report a prevalence ranging from 21–92% (Table ) . This wide variation likely is related to different stages of disease, lack of information in the medical records about appetite in retrospective studies, and a variety of other factors.…”
Section: Prevalence Of Weight Loss Body Composition and Reduced Appmentioning
confidence: 99%
“…Retrospective studies providing data on decreased appetite in cats with CKD report a prevalence ranging from 21-92% (Table 1). [1][2][3]5,7,8 This wide variation likely is related to different stages of disease, lack of information in the medical records about appetite in retrospective studies, and a variety of other factors. One study that surveyed 1079 owners of cats with CKD reported a prevalence of "abnormal appetite" in 43% of affected cats, 8 and the mean appetite score was 5.5 AE 2.2, where 1 = no food intake and 10 = normal appetite (unpublished data).…”
mentioning
confidence: 99%
“…This low palatability may compromise compliance with supplement use in patients and owners and may help explain the very poor market penetration of CKD supplements [22,23]. For the products containing IPB, the lack of palatability could be easily explained by the nature of IPB, which are known to have a lack of smell and taste: mostly they are simple molecular entities or polymeric structures able to form insoluble compounds with digestible phosphorus.…”
Section: Discussionmentioning
confidence: 99%